Effects of workers' hand washing and knife disinfection practices on microbiological quality of small animal carcasses in slaughterhouse environment - Durmusoglu, Halil; Incili, Gokhan Kursad; Demir, Pelin; Ilhak, Osman Irfan (Wiley, 2020)
The aim of this study conducted in two slaughterhouses was to reveal the effect of workers' hand washing and knife disinfection practices in reduction of microbial contamination on small animal carcasses. Hand washing and immersing blade into hot water (>= 82 degrees C for 5 s) practices resulted in significant reductions in microorganism counts of the workers' hands and knives and provided 0.1-0.7 log(10)and 0.5-1.0 log(10)/cm(2)decreases in TVC andEnterobacteriaceaecounts on the carcasses, respectively (p < .05). However, it was seen that still a high number of microorganisms remained on the workers' hand and blades after the hand washing and blade disinfecting practices. Although these practices are important and must be applied, it can be said that they are partly effective in reducing of microbial contamination of carcasses. Practical applications The EU approach favors the use of strict hygiene measures to lessen the microorganisms on the carcass surface, and refers that there is no need for carcass decontamination with chemicals when the hygienic measures are applied in slaughtering process. Also, there is an argument that decontamination procedures may mask poor hygiene during slaughtering. This study, provides knowledge about effect of hygiene practices on small animal carcasses microbiological quality in real slaughterhouse conditions.
Keywords: Escherichia-Coli; Contamination; Efficacy; Hygiene; Knives; Water